Introduction of covid-19 in early childhood through traditional game of congklak - Husna, Amalia; Suryana, Dadan (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2022)
Covid-19 cases are increasing every day and there is a spike in cases between late January and early February in 2020. According to the Indonesian Pediatrician Association, the rate of transmission of the Covid-19 virus to children in Indonesia is high, and parents must apply a high level of vigilance. in children. Learning in young children requires concrete objects, because children know the concepts of using symbols and learn with conditions that exist in real a situations or problems experienced in everyday life. The Congklak game can be one way to introduce Covid-19 to children with the principle of introducing concepts using symbols. This study aims to describe the ability of children to introduce Covid-19 at an early age through the game of congklak. This type of research is descriptive qualitative research. The subjects in this study were children in PAUD Permata Bunda, Koto Iman Village, who returned 20 children aged 4-6 years. Data was collected by observation or direct observation and interviews. The results of the study show that children have a good understanding of Covid-19 by introducing Covid-19 to early childhood through the game of Congklak. This can be seen when children are interviewed after simulating the spread and prevention of Covid-19 transmission, through the game of Congklak, children are able to recognize symptoms, how to spread and how to prevent Covid-19 that can be done.